Acute and chronic effects of high-intensity interval training on selected exerkine secretion in health, disease, and aging: a systematic review - Jost, Zbigniew; Rozynkowska, Agata; Głąb, Michalina; Sitkiewicz, Alicja; Goiko, Mia; Laskowski, Radosław; Herold, Fabian; Radák, Zsolt; Kujach, Sylwester (Frontiers in Physiology, 2026)
IntroductionIn contemporary research practice, high-intensity interval training (HIIT) has received growing attention compared to other types of endurance training [e.g., moderate-intensity continuous training (MICT)]. This is primarily related to HIIT’s ability to induce higher metabolic stress, driving an increased exerkine secretory response (i.e., of specific proteins) compared to MICT. To date, previous reviews on HIIT have primarily focused on single exerkines, while a more comprehensive analysis, as required to gain a more comprehensive understanding of the complex exercise-related physiological processes, is absent.MethodsTo reduce non-exercise protocol-related outcome heterogeneity, the rigorous inclusion criteria (i.e., exercise intensity in the HIIT adjusted for the target population of healthy, diseased, or older individuals, and not taking any medications) were applied.ResultsA total of 39 studies were selected for the systematic review, with fourteen, twenty-two, and three for the acute, chronic, and both acute and chronic effects of HIIT on exerkine concentrations, respectively. Acute HIIT appears to result in greater changes in BDNF and VEGF concentration than the control group performing lower-intensity exercise or no exercise. Metabolically active exerkine, such as adiponectin, mainly fluctuates among overweight and obese participants.DiscussionThis systematic review did not yield any definitive results regarding alterations in IGF-1, irisin, cortisol, and interleukin levels. Tendentially, HIIT is more effective than MICT and non-exercise interventions to induce a greater secretory response of certain exerkines, such as BDNF, VEGF and adiponectin. Evidence regarding exerkine secretion in response to HIIT among older adults remains limited, highlighting the need for further investigation.Systematic Review RegistrationIdentifier CRD420251003743.